Pengaruh pengumuman dividen terhadap harga saham sebelum dan sesudah ex-dividend date di Bursa Efek Indonesia - HASAN, Abdullah ([Yogyakarta] : Universitas Gadjah Mada, 2008)
This research objective is to analyze the influence of ex-dividend date announcement in the Indonesia Stock Exchange by taking 100 samples of shares. There are tree kinds of samples, increasing dividend, decreasing dividend and fix dividend. The method used in this research is event study that observe the stock price movement in the capital market. To examine the existence of price reaction, the abnormal return test will be conducted during the event period and the abnormal return test to the increasing dividend, decreasing dividend and fix dividend at the ex-dividend date. The result indicate that at the significant level of 5%, there are one working days which yield the abnormal return that is significant at the increasing dividend. Those are one day at t-2 before the event date with the value of 0.01830 or around 0.2%, Whereas the decreasing dividend reveals that there are one days that deliver the abnormal return which is significant. Those are one day at t+4 after the event date with the value of 0.02328 or approximately 2% and at fix dividend all data not significant. The final conclusion is that stock price will positively reacted to the announcement of increasing dividend at the ex-dividend date and negatively reacted to the announcement of the decreasing dividend at the ex-dividend date